Gestational Diabetes Mellitus Is Associated with Altered Neutrophil Activity - Stoikou, Maria; Grimolizzi, Franco; Giaglis, Stavros; Schäfer, Günther; van Breda, Shane Vontelin; Hoesli, Irene Mathilde; Lapaire, Olav; Huhn, Evelyn A.; Hasler, Paul; Rossi, Simona W.; Hahn, Sinuhe (Frontiers in Immunology, 2017)
Gestational diabetes mellitus (GDM) is a unique form of glucose intolerance, in that it is transient and solely occurs in pregnancy. Pregnancies with GDM are at high risk of developing preeclampsia (PE), a leading cause of fetal and maternal morbidity or mortality. Since PE is associated with excessive activation of circulatory neutrophils and occurrence of neutrophil extracellular traps (NETs) in affected placentae, we examined these features in cases with GDM, as this could be a feature linking the two conditions. Our data indicate that neutrophil activity is indeed altered in GDM, exhibiting pronounced activation and spontaneous generation of NETs by isolated neutrophils in in-vitro culture. In this manner, GDM may similarly affect neutrophil behavior and NETs formation as witnessed in other forms of diabetes, with the addition of the physiological changes mediated by pregnancy. Since circulatory TNF-α levels are elevated in cases with GDM, a feature also observed in this study, we examined whether this pro-inflammatory cytokine contributed to neutrophil activation. By using infliximab, a clinically utilized TNF-α antagonist, we observed that the pro-NETotic effect of GDM sera was significantly reduced. We also detected pronounced neutrophil infiltrates in placentae from GDM cases. The occurrence of NETs in these tissues is suggested by the extracellular co-localization of citrullinated histones and myeloperoxidase. In addition, elevated NE mRNA and active enzymatic protein were also detected in such placentae. This latter finding could be important in the context of previous studies in cancer or diabetes model systems, which indicated that NE liberated from infiltrating neutrophils enters surrounding cells, altering cell signaling by the degradation of IRS1. These findings could potentiate the underlying inflammatory response process in GDM and possibly open an avenue for the therapeutic interventions in gestational hyperglycemia.